2018
DOI: 10.1007/s11655-017-2428-6
|View full text |Cite
|
Sign up to set email alerts
|

Rules of Meridians and Acupoints Selection in Treatment of Parkinson's Disease Based on Data Mining Techniques

Abstract: The application of meridians and acupoints for PD treatment lay emphasis on the acupoints on the head, attach importance to extinguishing Gan wind, tonifying qi and blood, and nourishing sinews, and make good use of superior-inferior acupoints matching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…It has been estimated that more than one-third of the patients with PD in the United States (40%) and the United Kingdom (38.7%) have already accepted at least one form of complementary and alternative medicine for PD, whereas 7%–10% of them have used acupuncture and moxibustion [13]. It was recently shown that moxibustion can postpone the progression of PD and decrease the symptom severity [14, 15]. Additionally, it has been shown to enhance the protective effect of dopamine neurons in patients with PD [16, 17].…”
Section: Introductionmentioning
confidence: 99%
“…It has been estimated that more than one-third of the patients with PD in the United States (40%) and the United Kingdom (38.7%) have already accepted at least one form of complementary and alternative medicine for PD, whereas 7%–10% of them have used acupuncture and moxibustion [13]. It was recently shown that moxibustion can postpone the progression of PD and decrease the symptom severity [14, 15]. Additionally, it has been shown to enhance the protective effect of dopamine neurons in patients with PD [16, 17].…”
Section: Introductionmentioning
confidence: 99%
“…Another important finding of this study is that moxibustion treatment of Shi's moxa stick can effectively suppress dopaminergic neurons' death. As a form of external therapy in traditional Chinese medicine, moxibustion treatment reported can ameliorate motor symptoms in PD patients [9,10]. Shi's moxa sticks were developed by Shi Xuemin, an academician of the Chinese Academy of Engineering and a master of traditional Chinese medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Moxibustion is a form of external therapy in traditional Chinese medicine [8]. Recent research suggested that moxibustion treatment can postpone PD progression and has an apparent therapeutic effect on motor symptom improvement in PD patients [9,10]. Moreover, numerous animal experiments have confirmed that moxibustion can alleviate PD injury.…”
Section: Introductionmentioning
confidence: 99%
“…Since acupuncture therapy is clinically practiced based on acupuncture point combinations, association rules analysis is suitable to investigate the underlying rules of acupuncture point selections. The previous studies using data mining methods revealed the core combinations of acupuncture points in treating various neurological disorders, such as Parkinson's disease (Li et al, 2020a), vascular dementia (Feng et al, 2015), and Alzheimer's disease (Yu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%